Altered lipid metabolites accelerate early dysfunction of T cells in HIV-infected rapid progressors by impairing mitochondrial function - Li, Si-Yao; Yin, Lin-Bo; Ding, Hai-Bo; Liu, Mei; Lv, Jun-Nan; Li, Jia-Qi; Wang, Jing; Tang, Tian; Fu, Ya-Jing; Jiang, Yong-Jun; Zhang, Zi-Ning; Shang, Hong (Frontiers in Immunology, 2023)
The complex mechanism of immune-system damage in HIV infection is incompletely understood. HIV-infected “rapid progressors” (RPs) have severe damage to the immune system early in HIV infection, which provides a “magnified” opportunity to study the interaction between HIV and the immune system. In this study, forty-four early HIV-infected patients (documented HIV acquisition within the previous 6 months) were enrolled. By study the plasma of 23 RPs (CD4+ T-cell count < 350 cells/µl within 1 year of infection) and 21 “normal progressors” (NPs; CD4+ T-cell count > 500 cells/μl after 1 year of infection), eleven lipid metabolites were identified that could distinguish most of the RPs from NPs using an unsupervised clustering method. Among them, the long chain fatty acid eicosenoate significantly inhibited the proliferation and secretion of cytokines and induced TIM-3 expression in CD4+ and CD8+ T cells. Eicosenoate also increased levels of reactive oxygen species (ROS) and decreased oxygen consumption rate (OCR) and mitochondrial mass in T cells, indicating impairment in mitochondrial function. In addition, we found that eicosenoate induced p53 expression in T cells, and inhibition of p53 effectively decreased mitochondrial ROS in T cells. More importantly, treatment of T cells with the mitochondrial-targeting antioxidant mito-TEMPO restored eicosenoate-induced T-cell functional impairment. These data suggest that the lipid metabolite eicosenoate inhibits immune T-cell function by increasing mitochondrial ROS by inducing p53 transcription. Our results provide a new mechanism of metabolite regulation of effector T-cell function and provides a potential therapeutic target for restoring T-cell function during HIV infection.